Sanksi Hukum Terhadap Pelaku Tindak Pidana Memposting Konten Video Penistaan Agama Melalui Tiktok - Ni Luh Niken Ayu Tresna; I Nyoman Gede Sugiartha; I Made Minggu Widyantara (Jurnal Preferensi Hukum, 2025)
To ensure legal certainty in society, the law is responsible for the right of every citizen to obtain a defense before the law. With this rapid advancement in the field of technology and communication, social media is one of the technologies that allow everyone to move freely and greatly help human activities today. TikTok is one of the social media used for creativity. Many cases of blasphemy or blasphemy occur on social media today, consisting of insults or hate speech directed at individuals or groups related to ethnicity, religion, race, or intergroup (SARA). This can cause intolerance and can cause feelings of hatred towards fellow humans. This criminal offense is regulated in Articles 156 and 156a of the Criminal Code (KUHP) and the same regulation on blasphemy through social media is Article 28 paragraph (2) of Law Number 19 Year 2016. In addition, criminal sanctions are regulated in Article 45A paragraph (2) of the Electronic Information and Transaction Law.